Evaluation of disease and medication knowledge levels of diabetic patients - Umar, Rashida Muhammad; Çattık, Büşra Nur; Aslan, Selim (Istanbul University, 2023)
Background and Aims: Diabetes mellitus is a public health problem with a significant economic burden to society. Patient attitude is a significant determinant of adherence and clinical outcomes. We aimed to evaluate the disease and medication knowledge level of diabetic patients and possible patient-related predictive factors. Methods: Adult diabetic patients were included in the study. Patients' demographic and health-related data were collected using a pre-prepared form. Two questionnaires, KAP knowledge tool and Medication Assessment tool were used to assess the disease and medication knowledge levels of patients. Results: The mean age of 159 patients was 54.44 & PLUSMN;12.24 years. The disease and medication knowledge scores were high with an average of 13.9 & PLUSMN;1.74 and 5.26 & PLUSMN;0.53, respectively. Higher scores were linked to being male (p=0.042; p=0.007) and higher educational status (p<0.001; p=0.006). Lower scores were recorded in patients with comorbidities (p=0.002; p<0.001), older patients (p<0.001), longer disease duration (p<0.001; p=0.009), longer antidiabetic drug use (p<0.001; p=0.009) and using more drugs (p=0.002; p=0.006). None of the patients could mention any possible side effects of their medications. Conclusion: It can be deduced that patient-related factors are significant predictors of patients' disease and medication knowledge. Patient-specific education in addition to rational pharmacological intervention is necessary to achieve better clinical outcomes.
Keywords: Diabetes Mellitus; Disease Knowledge; Medication Knowledge; Patient Factors